Production simulation and prediction of fractured horizontal well with complex fracture network in shale gas reservoir based on unstructured grid - Xiao, Hongsha; Chen, Man; Jing, Cui; Zhao, Huiyan; Wang, Keren (Frontiers in Earth Science, 2023)
Abstract：In order to accurately simulate the productivity variation characteristics of fractured wells with complex fracture network in shale gas reservoir, based on the multiple migration mechanism of shale gas, the micro-seismic data and discrete fracture model were used to characterize the fracture geometry and complex boundary characteristics, and the comprehensive seepage mathematical model of fractured wells with complex fracture network was established based on the dual porosity-discrete fracture model, and the numerical solution was carried out by combining the unstructured grid and the control volume finite element method. The sensitivity analysis of the influence of key parameters such as fracture conductivity, physical property difference in composite area and Langmuir volume on the production performance of fractured horizontal wells is carried out. This study provides theoretical methods and calculation tools for accurate prediction of productivity change and optimization of production system of fractured horizontal wells with complex fracture network in shale gas reservoirs.